ANALISIS SKALA PRIORITAS PENANGANAN UJI KELAIKAN FUNGSI JALAN DITINJAU DARI ASPEK TEKNIS PENDEKATAN KUANTITATIF ANALYTIC HIERARCHY PROCESS (STUDI KASUS: JALAN LINTAS SUMATERA TANJAKAN TARAHAN) - Catur Marina, Bernaditha; Hermon Frederik Tambunan; Sri Hendarto; Jimmael Martogi Hutagaol (Yayasan Nusantara Hasana Berdikari, 2025)
The rapid population growth in Bandar Lampung has led to an increase in vehicle ownership, which necessitates the provision of adequate road infrastructure and facilities. According to the Regulation of the Minister of Public Works No. 11/PRT/M/2010 concerning Guidelines and Requirements for Road Function Feasibility, road functionality is classified into three categories: Feasible (LF), Conditionally Feasible (LS), and Not Feasible (TLF). To determine the appropriate category of road functionality, the Analytic Hierarchy Process (AHP) method is employed. AHP is a decision support model involving selected respondents who are knowledgeable about the assessed road segment and the criteria for road feasibility. The respondents in this study include representatives from road authorities (Ministry of Public Works and Housing), traffic authorities (Indonesian National Police), transportation agencies (Ministry of Transportation), as well as members of the public, students, and academics. Based on the analysis, the AHP-LFJ score for the Kalianda–Tarahan road segment is 0.696 (approximately 69%), which corresponds to the category of Conditionally Feasible (LS) according to the AHP-LFJ classification thresholds: LF (100%), LS (0.99–0.67), LT (0.66–0.33), and TLF (≤0.32). Roads categorized as Conditionally Feasible (LS) meet part of the technical requirements and are still considered safe for road users.